Interface-Induced WSe2 In-plane Homojunction for High-Performance Photodetection - Jiawei Chi; Nan Guo; Yue Sun; Guohua Li; Lin Xiao (Nanoscale Research Letters, 2020)
Abstract 2D transition metal dichalcogenides (TMDCs) have been extensively attractive for nano-electronics and nano-optoelectronics due to their unique properties. Especially, WSe2, having bipolar carrier transport ability and sizable bandgap, is a promising candidate for future photodetectors. Here, we report an in-plane WSe2 homojunction formed by the interface gate of the substrate. In this architecture, an insulated h-BN flake was used to make only part of WSe2 flake contact substrate directly. Finally, the structures of WSe2/substrate and WSe2/h-BN/substrate construct an in-plane homojunction. Interestingly, the device can operate in both photovoltaic and photoconductive modes at different biases. As a result, a responsivity of 1.07 A W−1 with a superior detectivity of over 1012 jones and a fast response time of 106 μs are obtained simultaneously. Compared with previously reported methods adopted by chemical doping or electrostatic gating with extra bias voltages, our design provides a more facile and efficient way for the development of high-performance WSe2-based photodetectors.